Quality of solid and liquid oils in food applications: Insights from slip melting point and iodine value - Lestari, Puji; Yusuf, Faisal; Furqan, Mainal (Journal of Midwifery and Nursing, 2026)
This study's main objective was to assess and compare the quality of liquid and solid oil on their iodine value (IV) and slip melting point (SMP). This study employed a comparative experimental design, in which liquid oil (palm olein) and solid oil (a blend of palm olein and palm stearin) were analyzed under controlled laboratory conditions. Standardized analytical methods were used to ensure reliable comparison between oil types. AOCS Official Method Cc 3-25 was used to calculate the SMP, and the Wijs method was used to measure the IV in accordance with AOCS Official Method Cd 1-25. IV solid oil are 51.80, 52.35 and 52.76 (? = 52.30),  SMP solid oil are 37.4, 37.8 and 37.4 (  IV liquid oil are 58.59, 58.55 and 58.11 (? = 58.42), SMP liquid oil are 19.6, 19.6 and 19.8 ( . In conclusion, liquid oil is higher iodine value that means greater content of Unsaturated fatty acids are linked to positive cardiovascular health outcomes. Solid oil, on the other hand, showed a higher slip melting point, which implies greater thermal stability and makes it more appropriate for high-temperature frying applications.